Analisis Sentimen Publik Terhadap Implementasi Program Pendidikan Karakter Berbasis Barak Militer Di Jawa Barat - Diki Suherman; Ami Afriyani; Nanang Suparman; Taufiq Rahmat (UIN Sunan Gunung Djati Bandung, 2026)
The increasing cases of juvenile delinquency, student brawls, and behavioral problems in West Java led to the introduction of the Military Barracks Education policy as a measure to strengthen student discipline and character. The policy has triggered significant public debate, especially on social media, making it important to understand how the public responds. This study aims to analyze public sentiment toward the policy through Instagram user comments. Data were collected using a web-crawling technique with Instant Data Scraper, resulting in 8,169 comments from various related posts. All data underwent text preprocessing and were analyzed using the IndoBERT model to classify sentiments into positive, negative, and neutral categories. The findings indicate that negative sentiment dominates with 3,639 comments, followed by 3,320 positive and 1,210 neutral comments. Negative sentiment primarily reflects concerns about psychological risks, potential stigma, and the lack of transparency in participant selection, while positive sentiment highlights support for improving student discipline. These results show that the Military Barracks Education policy remains controversial and requires further evaluation to align with humanistic education principles and child protection standards.